Internet of Things: redefinition of Business Models for the next generation of Telecom services - Amirhossein Ghanbari; Óscar Álvarez; Jan Markendahl (International Telecommunications Society (ITS), 2015)
This paper provides an assessment of existing M2M business models and arrangements in selected industry segments. It studies the drivers and barriers for adaption of M2M and IoT in transforming operations in the selected industry segments, and focusses on identifying recurring patterns in the transformation process. The change in value propositions as well as how value networks transform is studied and analysed. The studied segments and services are: - Public transportation services, - Automotive and vehicle related services, - Smart energy services, - Health care and home care services. The analysis has targeted business modelling KPIs of the type “Business application cases” and includes two different cases; one for a mobile operator and one for a system and network equipment manufacturer. In both cases the description focuses on the identified business opportunities for the actors and the required actions that are identified in order to exploit the opportunities, the following aspects are included: - The set of features that can be offered to end users, - Capabilities, resources or knowledge to develop, - Business relations to exploit and develop, - Change of position in the value network, - Potential conflicts (with partners, customers and internally) to handle. All of these items are clearly related to transformation of the business and hence a change for the involved actors and their customers, suppliers and partners. In summary the findings of the analysis are as follows: For drivers and benefits the common themes from the cases are that users get a value of being connected and/or to be available and/or to be able to collect data or perform activities on the move. Identified barriers include challenges related to acquiring new competences about services and application areas and to build up and maintain new customer relations.. Also the number of customers at a market (national or global) is a key issue. A mobile operator may be able to have business relations with 10 big actors but not with 100 or 1000 smaller actors. The same applies for telecom vendors that are used to handle a limited number of big customers. In addition to new competences and ability to handle customer relations a key to success is to be able to change market position.
Keywords: 330